Problem-Based Learning (PBL) Awareness among Academic Staff in Universiti Tun Hussein Onn Malaysia (UTHM) - Najah Ramlan; Zulida Abdul Kadir; Hani Suraya Aziz; Iza Nurhidayah Ismail; Nurul Sabrina Zan; Khairul Firhan Yusob; Ahmad Nazri Jelani (PAROLE: Journal of Linguistics and Education, 2020)
The present study was conducted to determine whether the academic staff in UTHM was aware of Problem-based Learning (PBL) as an instructional approach. It was significant to identify if the academic staff in Universiti Tun Hussein Onn Malaysia (UTHM) had the knowledge about PBL. It was also crucial to know if the academic staff was aware of PBL as a method of teaching their courses in class as this could give the feedback to the university on the use of PBL among academic staff and measures to be taken to help improve their teaching experience. A workshop could also be designed if the academic staff in UTHM was interested to know more about PBL and how it could be used in their classroom. The objective of this study was to identify the awareness of PBL among academic staff in UTHM. This study was conducted via a quantitative method using a questionnaire adapted from the Awareness Questionnaire (AQ). 100 respondents were involved in this study. The findings indicated that the awareness of PBL among UTHM academic staff was moderate. In conclusion, the academic staff in UTHM has a moderate level of knowledge about PBL as a teaching methodology.